ANALISIS KESALAHAN PENGGUNAAN TANDA BACA DALAM TEKS NARASI BUKU BAHASA INDONESIA KELAS IV KURIKULUM MERDEKA - Ulayya, Salma; Rahmawati, Fitri Puji (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
The purpose of this study is to determine and describe the form of punctuation errors in narrative texts in student books Buku Bahasa Indonesia SD Kelas IV Kurikulum Merdeka. This research is a descriptive qualitative research. The data collection technique used is to listen and record.Â  Researchers conducted a listening technique by carefully reading 12 narrative texts in the Buku Bahasa Indonesia SD Kelas IV Kurikulum Merdeka, then recorded and classified according to the form of error. Intrarater and interether techniques are used to test the validity of the data. Data analysis techniques in this study consist of data collection, data reduction, data presentation, and conclusions. The results showed a total of 7 errors in the use of punctuation. These errors are 1 period error, 3 comma errors, 1 colon error, 1 quotation mark error, and 1 single quotation error. Commas are the punctuation marks with the most usage errors. The use of punctuation in textbooks needs to be considered again, adjusting to existing writing rules.